2015
DOI: 10.1080/13683500.2015.1072503
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with medical travel behaviours: the input–process–output perspective

Abstract: This study adopts the input-process-output perspective to develop a research framework, and aims to investigate the factors associated with medical travel behaviours. A total of 343 international medical tourists who took low invasive treatments in Taiwan were surveyed using questionnaires. The data were analysed using structural equation modelling, and the results of this work are as follows. Medical tourists felt that higher service quality led to better corporate image. The service quality and corporate ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…The argument is that transformational leaders may successfully promote and encourage the adoption of regulatory frameworks that foster creative problem-solving and tactical flexibility. This viewpoint is consistent with Lu and Wu's (2018) interactive control systems theory, wherein managers encourage staff members to question presumptions and offer original ideas. H1: levers of controls (LOC) positively affect competitive advantage (CA).…”
Section: 1supporting
confidence: 69%
“…The argument is that transformational leaders may successfully promote and encourage the adoption of regulatory frameworks that foster creative problem-solving and tactical flexibility. This viewpoint is consistent with Lu and Wu's (2018) interactive control systems theory, wherein managers encourage staff members to question presumptions and offer original ideas. H1: levers of controls (LOC) positively affect competitive advantage (CA).…”
Section: 1supporting
confidence: 69%
“…Secondly, this model is highly structured, with clear distinctions between inputs, processes and outputs. This clarity helps in identifying the components at each stage and understanding their relationships, which, in turn, leads to a more comprehensive picture of the situation (Lu and Wu, 2018). Thirdly, many studies have proved that the IPO model can be used to analyse the process of online learning and the factors that impact student performance.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…This is because medical services are high in credence properties, which are attributes that make them difficult to assess without a unique level of skills and background knowledge specific to medical treatment [ 43 ]. Furthermore, previous research has indicated that medical tourists consider the perceived quality of medical care as the most critical attribute for destination selection [ 10 , 44 ], and according to [ 45 ], higher levels of perceived quality of medical care from a medical facility leads to a better corporate image of that same medical provider.…”
Section: Literature Reviewmentioning
confidence: 99%